Valoración de los Indicadores de Sostenibilidad bajo los lineamientos de la FAO para la Universidad Técnica de Cotopaxi Campus CEASA. - Borja Saltos, Deyvi Alexander (2020)
This study selects environmental sustainability indicators and sustainable development in accordance with FAO guidelines, which can be applied in the sustainability process in the CEASA university campus. Indicators created as a system of tools that allow assessing the progress of institutional management towards sustainable development. Being a conceptual, methodological and instrumental development, it was considered appropriate to provide an overview of the indicators in the four sustainability domains, namely, Governance, Economic, Environmental and Social. In recent years, there has been a significant progress in the field of indicators for decision-making, presenting initiatives that include different scales and different approaches, while recently others have been working from sustainable development. During this research, meetings were held with local experts in the field of sustainability, to whom surveys, and interviews based on the Delphi method were applied for the selection and subsequent characterization of appropriate indicators for the campus. Obtaining the following: 94 of the 116 indicators contained in SAFA method were selected and characterized by the experts. It was determined that 17 indicators belong to the Administrative Sustainability domain with 89% of accepted indicators, 48 indicators bel0ng to the Environmental Integrity domain with 92% of selected indicators, 17 indicators belong to the Economic Resilience domain with 65% of selected indicators and 12 indicators belong to the Social Welfare domain with 63% of indicators considered suitable for application in the campus.